Diagnóstico del sistema de seguridad, salud y bienestar ocupacional en la Cooperativa de Ahorro y Crédito Calceta limitada del cantón Bolívar - Cano Resabala, Ida Yolanda (2020)
The present investigation was developed in the Cooperativa de Ahorro y CrédiCalceta Ltda. of Bolívar canton and aimed to diagnose the occupational safety, health and well-being system to contribute to the improvement of the activities of its workers and collaborators. For the development of the research, the deductive, inductive and analytical method was used, which helped to systematize the research and help achieve the established objectives. Techniques such as the interview and the survey were applied to the administrative and service personnel of the institution, which allowed collecting data and obtaining information on the current situation of the institution in terms of the conditions and existing risk factors and, from there, search alternative solutions. It was possible to determine that the workers and collaborators of the Cooperative face labor risks in the development of their activities since there is no periodic control of the health and safety system. The use of the PGV or triple criteria matrix tool made it possible to objectively establish the relevant risks and analyze them in order to propose concrete actions to reduce them. For the application of the improvement plan, the 5W + 1H method was used as a tool that allowed identifying the causes of the existing risks and proposing solution strategies for the prevention of accidents and occupational diseases, in a way that contributes to health, safety and well-being of workers and the efficient performance of their functions to meet the expected objectives.